Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s003118201900177x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteric parasite of wild Galliformes in the Italian Alps: implication for conservation management

Abstract: This study provides insights about the diversity, prevalence and distribution of alpine wild galliformes gastrointestinal parasite community, trying to fill a gap in the scientific information currently available in scientific literature. The analysis included three host species: 77 rock partridge (Alectoris graeca saxatilis), 83 black grouse (Tetrao tetrix tetrix) and 26 rock ptarmigan (Lagopus muta helveticus) shot during the hunting seasons 2008–2015. Parasites isolated were Ascaridia compar, Capillaria cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
3
13
1
Order By: Relevance
“…This is likely to be due to the climatic conditions required for sporulation and survival of oocystis (Tenter et al., 2000), with humidity and moderate temperatures playing an important role (Smith & Frenkel, 1995). Overall, this result is in accordance with other recent studies in other species, demonstrating a geographical variations of parasite infestation under different climatic condition (Fanelli et al., 2020; Rostami et al., 2017; Sanchis‐Monsonís et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…This is likely to be due to the climatic conditions required for sporulation and survival of oocystis (Tenter et al., 2000), with humidity and moderate temperatures playing an important role (Smith & Frenkel, 1995). Overall, this result is in accordance with other recent studies in other species, demonstrating a geographical variations of parasite infestation under different climatic condition (Fanelli et al., 2020; Rostami et al., 2017; Sanchis‐Monsonís et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have evaluated the impact of environmental factors on the development, survival and distribution of parasites characterized by a cycle with free-living stages (Stromberg, 1997;O'Connor et al, 2006); however, very few studies have been carried out on wildlife for such long period of time (Iacopelli et al, 2020). Our finding is in line with the study of Fanelli et al (2020) who found a higher prevalence of gastrointestinal parasites in wild Galliformes living at higher latitude. As in this study, these authors interpreted latitude as a proxy of the climatic and environmental conditions required for the development of free-living stages of the parasite.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with Fanelli et al (2020), who have found the Rock ptarmigan living in the Italian Alps free of parasites, this study presents a parasite richness higher than the one detected by Zbdinden and Hoerning (1985) and similar, in terms of different parasite genus, to the one detected by Holmstad et al (2005) in Norway and Skirnisson et al (2012) in Iceland. However, a comparison with these studies is difficult, due to the different epidemiological situations of the ptarmigan populations, and due to the distinct population and environmental conditions.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In this study, the maximum altitude recorded for a heartworm-positive wolf was c .350 m above sea level, corresponding to hill zones at the limit with low mountains. In this regard, environment and climate influence on parasite distribution is commonly described [ 38 , 39 ]. Further explanation for the low prevalence in investigated wolves is the age structure, with juveniles (< 12 months) summing up to one third of the sample (38.1%) (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%